Spectral luminescent properties of bacteriochlorin and aluminum phthalocyanine nanoparticles as hydroxyapatite implant surface coating - Yu. S. Maklygina; A. S. Sharova; B. Kundu; V. K. Balla; R. Steiner; V. B. Loschenov (Biomedical Photonics, 2016)
The development and the spectral research of unique coating as crystalline nanoparticles of IR photosensitizers were performed for the creation of hydroxyapatite implants with photobactericidal properties. It has been proved that by the interaction of nanoparticles covering implant with the polar solvent, which simulates the interaction of the implant with the biocomponents in vivo (fast proliferating and with immunocompetent cells), photosensitizers nanoparticles change the spectroscopic properties, becoming fluorescent and phototoxic. Thus, the developed coating based on crystalline photosensitizer nanoparticles with studied specific properties should have antibacterial, anti-inflammatory effect by the photodynamic treatment in the near implant area. This research opens the prospect of the local prevention of inflammatory and autoimmune reactions in the area of implantation. The results of the study suggest a promising this technology in order to create implants with photobactericidal properties.